Virtual Laboratory: Development of Physics Practicum Instruction to Improve Student Skills - Fitriya S; Maiyanti, Aziza Anggi (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2023)
This project aims to provide students with lab practice that is completely genuine, to learn about their practice habits, and to inspire them to study after utilizing the created physics lab practice. This study is a type of development utilizing physics lab practice use 4-dimensional learning tools. Utilizing confirmation of reasoning, observation, and questionnaire. The evaluation of the virtual lab yielded the logic validation value 2,78 and they are considered reliable and safe for usage as a trial for development. The development testing revealed that the students work passed muster with the help of the physics virtual laboratory baseds instructions, either on the capacity for observation and note taking or the capacity for interpretation and illustration. The results of the development test showed that the students practicum performance in all practicums, in the aspect of ability to observe and record practicum results, was in the good category with a range between 61.37% and 92.93%, and in the aspect of ability to interpret the results and formulate conclusions, it was categorized as good with a range between 65.15% and 96.97%. The virtual laboratory based physical practicum instructions that were developed obtained validity in the good category and are suitable for use as a guide for physical teachers and students in carrying out practicums.